Діяльність Асоціації американських медичних коледжів у 1901-1905 рр. - Куліченко, Алла Костянтинівна; Kulichenko, Alla (Хмельницька гуманітарно-педагогічна академія, 2018)
У дослідженні зосереджено увагу на висвітленні питання про діяльність Асоціації американських медичних коледжів під час реформи медичної освіти США у 1901-1905 рр. Зокрема, розглянуто поправки до статті ІІІ конституції Асоціації, що було внесено впродовж 1901-1905 рр.; систематизовано та представлено загальні резолюції (рекомендації) засідань Асоціації у зазначений період. Визначено, що статтю ІІІ конституції Асоціації американських медичних коледжів присвячено вимогам для вступу до медичних шкіл США. Вдалося встановити, що на щорічних засіданнях Асоціації спеціально призначений комітет переглядав вказану статтю, враховуючи тогочасний стан медичної освіти та якість надання медичних послуг американському народу. Крім того, введено у вітчизняний науковий обіг чотири варіанти статті ІІІ конституції Асоціації американських медичних коледжів (1901-1905 рр.), виконано їх порівняльний аналіз. З’ясовано, що Асоціація не завжди ухвалювала загальні резолюції (рекомендації) засідань, про що свідчить їх відсутність у 1902, 1903 та 1905 рр. In the early 20th century, the American medical education experienced the so-called pioneering era in its development. Moreover, in 1901–1905, there was a social disappointment due to the poor medical services and the high mortality rate among the US population, which was caused by the incompetence of doctors. This situation contributed to the reform and led to the strengthening of the academic movement. The main participants of the movement were both various organizations and educators, with the Association of American Medical Colleges (AAMC) being one of these organizations. Note that there were no uniform admission requirements to American medical schools during the stated period. Thus, the author describes this issue that has been reflected in Article III of the AAMC Constitution as a part of the Association activity. The aim of the paper is to highlight the AAMC’s activities during the reform of the US medical education in 1901–1905. To achieve the aim and objectives of the study, the author deals with both general scientific and special methods, namely the heuristic and bibliographic method (to search, systematize and generalize the scientific and pedagogical works, archival documents and periodicals on the research problem); the content analysis and synthesis (to study and systematize the scientific and pedagogical literature on the research subject); the comparative-historical method (to compare four options of Article III of the AAMC Constitution from 1901 to 1905); the pedagogical reconstruction (to reproduce historical and pedagogical reality at the Association’s annual meetings concerning Article III of the AAMC Constitution, and the AAMC resolutions (recommendations) in the first five years of the 20th century). Moreover, the author represents four options of Article III of the AAMC Constitution that differ from each other. This fact points at the improvement of the admission requirements to medical schools, and at the serious attitude the academic community dedicated to the issues of population’s life and health. Note that the results of the AAMC annual meetings produced general resolutions (recommendations) concerning the educational process in medical schools and many other issues. As for the prospects of further scientific research, we are going to highlight the AAMC activities during the reform in the American medical education, and to reveal the importance of the AAMC as the educational association while interacting with other US educational organizations in the early 20th century.
The Association of American Medical Colleges: Activities in 1901–1905
Keywords: американська медична освіта; реформа; Асоціація американських медичних коледжів; діяльність; стаття ІІІ конституції; резолюція; рекомендація; вимоги для вступу; медична школа; American medical education, reform; Association of American Medical Colleges; activity; Article III of the Constitution; resolution; recommendation; admission requirements; medical school